2008
DOI: 10.1103/physrevb.77.224417
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance behavior of ferromagnetic shape memory alloyNi1.75Mn1.25Ga

Abstract: A negative-positive-negative switching behavior of magnetoresistance ͑MR͒ with temperature is observed in a ferromagnetic shape memory alloy Ni 1.75 Mn 1.25 Ga. In the austenitic phase between 300 and 120 K, MR is negative due to s-d scattering. Curiously, below 120 K MR is positive, while at still lower temperatures in the martensitic phase, MR is negative again. The positive MR cannot be explained by Lorentz contribution and is related to a magnetic transition. Evidence for this is obtained from ab initio de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 71 publications
8
38
1
Order By: Relevance
“…The reasons for this disagreement could be that the actual sample has Mn excess, which might cause Mn clustering leading to antiferromagnetic coupling between Mn atom pairs, as has been observed for other Mn excess systems. 22,32,33 Moreover, note that the theory does not consider the actual monoclinic structure (discussed below) which might favor a different magnetic ground state with anti-parallel coupling between Mn atoms.…”
Section: B Experimental Studiesmentioning
confidence: 99%
“…The reasons for this disagreement could be that the actual sample has Mn excess, which might cause Mn clustering leading to antiferromagnetic coupling between Mn atom pairs, as has been observed for other Mn excess systems. 22,32,33 Moreover, note that the theory does not consider the actual monoclinic structure (discussed below) which might favor a different magnetic ground state with anti-parallel coupling between Mn atoms.…”
Section: B Experimental Studiesmentioning
confidence: 99%
“…Among the different FSMA's discovered so far, Ni 2 MnGa is at the center of attention because of large (10%) magnetic field induced strain and interesting magnetic behavior. [15][16][17] It is an ideal model system to explore the co-existence of ferromagnetism and CDW because martensite transition (which is a diffusionless first order transition from high symmetry austenite phase to a lower symmetry martensite phase) is known to be associated with phonon anomalies.…”
Section: 6mentioning
confidence: 99%
“…It is seen that the positive saturation MR of ϳ26.6% is developed in the T-range from 260 to 315 K, while the negative saturation MR of ϳ25.2% is formed from 230 to 315 K. For comparison, Ni-Mn-Ga alloys usually show the largest MRs during the narrow martensitic-austenitic phase transformation. [10][11][12] Figure 5 shows the saturation MR as a function of spatial angle ͑ ͒ between H and I for different magnitudes of H at room temperature ͑298 K͒ based on the preset initial nearly single-variant state S. It is noted that the direction of H was maintained along the z-axis, while that of I was kept along the l-direction of the single crystal so that was obtained by rotating the single crystal ͑also I͒ with respect to H. It is found that the MR value varies periodically with . The saturation MR has a periodic change between 0 and ϳ−25% for every 180°or half cycle of .…”
Section: Resultsmentioning
confidence: 99%
“…It is argued that the underlying mechanisms are mainly governed by the s-d scattering for the bulks and the spin transport for the thin films. 10,11 Among the Heusler alloys, Ni-Mn-Ga single crystals exhibit giant magnetic field-induced strains ͑MFISs͒ of ϳ6% ͑load-free͒ in the tetragonal martensitic phase and of ϳ10% in the orthorhombic martensitic phase as a result of the martensitic twin-variant reorientation induced by magnetic field, mechanical stress, and/or temperature. [13][14][15] This reorientation may also lead to a characteristic change in electrical resistivity due to crystallographic anisotropy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation